HUBUNGAN STRES KERJA DENGAN KINERJA BIDAN SELAMA PANDEMIK COVID-19 DI KOTA PONTIANAK - Fajrin, Dessy Hidayati (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Work stress on midwives during the COVID-19 pandemic can occur due to high work demands, long working hours, mindset, limited number of health workers. While the number of patients continues to grow and work safety procedures continue to change along with the development of the virus COVID-19. If a midwife does not manage work stress properly this will have an impact on her performance in providing health services to patients. This study aims to analyze the relationship between work stress and the performance of midwives during the COVID-19 pandemic in Pontianak City in 2021. In order to find and analyze the relationship between work stress and midwife performance, it is used methods quantitative with adesign cross sectional. The sample of this research was 43 midwives in Pontianak City. Sampling withmethod total sampling. Data analysis uses univariate and bivariate. The results of this study were 23 respondents (53.5%) who experienced work stress and 20 respondents (46.5%) who did not experience work stress. On the performance of midwives there are 25 respondents (58.1%) with good performance and 18 respondents (41.9%) with poor performance. Based on the Chi-square test, the p value = 0.004 means that the sig value is smaller than 0.05 (0.004 <0.05) indicating that work stress is related to the performance of midwives during the COVID-19 pandemic in Pontianak City. So that work stress is related to the performance of midwives during the COVID-19 pandemic in Pontianak City.